INFLUENCE OF CLANISM ON INSTITUTIONAL LEADERSHIP IN PUBLIC SECONDARY SCHOOLS IN KAJIADO COUNTY, KENYA - Purdul, John N.; Thinguri, Dr. Ruth; Muiru, Dr. Anne (African Journal of Education and Practice, 2019)
Purpose: This study focused on investigating the influence of clanism on institutional leadership in public secondary schools in Kajiado County. The study was guided by the Social Identity Theory, the Theory of Institutional Leadership, and the Equity Theory. Methodology: The study adopted the mixed research methodology and the concurrent triangulation design. The target group involved 783 respondents comprising of 60 principals, 60 deputy principals, 655 public secondary schools teachers and 8 education officers. The sample size comprised 25 principals, 25 deputy principals, 5 education officers and 185 secondary school teachers. The study employed the simple random sampling techniques to select the education officers, deputy principals and teachers, purposive sampling for selection of principals and stratified sampling techniques for selection of public secondary schools. Questionnaires, interview guides and document analysis checklists were used to collect quantitative and qualitative data. Quantitative data yielded descriptive statistics which was analyzed using frequencies, percentages, means and standard deviation and presented using tables and charts. Inferential statistics was analyzed using multiple regressions and presented in tables. Qualitative data was analyzed thematically and presented in narrative form and quotations. Findings: The study confirmed that clanism influences institutional leadership as "people" place their clansmen/women in favourable positions for them to compete favourably for the scarce resources and available leadership and teaching positions. The study concluded that the influence of clanism was more pronounced in the rural areas than in cosmopolitan regions due to the in-migration of non-Maasai ethnic groups and the near-kin relationship over distant-kin relationship resulting from clanism is not an easy one to get rid of. Unique contributions to Theory, Practice and Policy: It is vital for TSC to identify, appoint and train the right people to be institutional leaders. The study recommended transparency, fair treatment and meritocracy to be upheld at all times by the Teachers Service Commission (TSC) and the Board of Management (BOMs) during the appointment, recruitment, selection and promotions of principals, deputy principals and teachers in the public secondary schools. In addition, the study recommended the full implementation of the TSC 2007 policy on identification, selection, appointment, deployment and training of heads of post primary institutions.